2020
DOI: 10.1037/aca0000242
|View full text |Cite
|
Sign up to set email alerts
|

Motivational processes that support arts participation: An examination of goal orientations and aspirations.

Abstract: In- and out-of-school participation in the arts has been shown to be positively associated with students’ academic and nonacademic outcomes. Despite this finding, little work has examined the motivational processes that underpin arts participation, either as separate types (e.g., active vs. receptive) or as an overarching factor. However, given the positive outcomes linked with arts participation, there may be yields in examining the motivational processes that foster arts participation over time. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 82 publications
(198 reference statements)
0
7
0
Order By: Relevance
“…According to Elliot, goals are a major means by which individuals' approach (and avoidance) orientations are manifested. Recent research has identified growth goals (i.e., self-improvement, or personal best goals) as one example of an approach motivation orientation (Martin and Liem, 2010 ; Elliot et al, 2011 , 2015 ; Martin and Elliot, 2016a , b ; Burns et al, 2018 , 2019 , 2020b ). We recognize mastery goals are also approach-oriented, but it has previously been argued that growth goals represent a particularly ambitious and challenge-oriented goal striving (in keeping with our intent to capture challenge orientation) and are shown to explain variance in engagement beyond the effects of mastery goals (Yu and Martin, 2014 ; Martin and Elliot, 2016a ).…”
Section: Lri and Accompanying Psychological Orientationsmentioning
confidence: 99%
“…According to Elliot, goals are a major means by which individuals' approach (and avoidance) orientations are manifested. Recent research has identified growth goals (i.e., self-improvement, or personal best goals) as one example of an approach motivation orientation (Martin and Liem, 2010 ; Elliot et al, 2011 , 2015 ; Martin and Elliot, 2016a , b ; Burns et al, 2018 , 2019 , 2020b ). We recognize mastery goals are also approach-oriented, but it has previously been argued that growth goals represent a particularly ambitious and challenge-oriented goal striving (in keeping with our intent to capture challenge orientation) and are shown to explain variance in engagement beyond the effects of mastery goals (Yu and Martin, 2014 ; Martin and Elliot, 2016a ).…”
Section: Lri and Accompanying Psychological Orientationsmentioning
confidence: 99%
“…Future research may consider building on this in two ways: first, researchers may consider examining if different profiles of participation exist across subdomains of science (e.g., physics, chemistry, and biology); second, researchers may consider examining if other such patterns of participation exist in other academic domains, such as English. Indeed, there is evidence for distinct patterns of active and receptive participation in arts education (Burns et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A second framework for distinction considers the level of interaction present in each activity, such that activities can involve low levels of interaction (i.e., receptive) or high levels of interaction (i.e., active). This conceptual framework (receptive vs. active) was initially developed and validated within arts education (Burns et al, 2020; Cuypers et al, 2012; Martin et al, 2013) and has clear alignments with multiple classification frameworks developed in science education (discussed below; Dabney et al, 2012; Dou et al, 2019; Nazier, 1993). Because nomenclature varies across these previously developed frameworks, a contribution of this study is the development of an integrated framework that offers conceptual clarity about how the level of interaction present in unstructured out‐of‐school science activities can be considered as either receptive or active.…”
Section: Understanding Participation In Out‐of‐school Science Activit...mentioning
confidence: 99%
See 1 more Smart Citation
“…We kick off the special issue with two studies that explored the impact of motivations on arts participation, including ways to reengage individuals in arts activities. Burns and colleagues (2020) found that in a large sample of Australian middle and high school students, growth goal orientations predicted arts aspirations and that arts aspirations in turn predicted arts participation. They concluded that growth goal orientations and arts aspirations may function as the motivational bases for supporting increased curriculum-related arts participation.…”
mentioning
confidence: 93%